Has the Balance Tipped? The Thai Military and its Security Perceptions in an Era of Asia-Pacific Great Power Competition - Deavenport, Joseph (Graduate Review of Political Science and Public Administration Journal, 2025)
Since 2017, the most significant change in Asia-Pacific regional affairs has been the rise of Great Power competition between the United States and China. This paper examines how the external securitization of the region, coupled with Thailand’s shifting internal dynamics, affected the security perceptions of military leaders within the Royal Thai Armed Forces. Using a comprehensive approach that includes documentary research, surveys of Thai military officers, and interviews, this research focuses on the Royal Thai Armed Forces as a perception forming entity and explores how external and internal security developments have influenced the Thai military’s perceptions. This research presents three key findings. First, Thai military leaders perceive Great Power states as much less threatening to Thai security than they did just a few years ago. Second, the Thai military continues to prioritize domestic security issues, reflecting a persistent focus on internal stability and national sovereignty over external threats. Third, the lack of cross-border conflicts in Southeast Asia during this period contributed to a decreased threat perception toward neighboring states, underscoring a preference for stability and non-alignment in the face of Great Power rivalry. This research contributes to a nuanced understanding of Thai security perceptions in a rapidly changing geopolitical environment. It highlights the complexities faced by Thailand as it navigates its strategic position between two great powers, seeking to balance relationships while maintaining its national security and autonomy. The findings offer valuable insights for policymakers and scholars interested in Southeast Asian security dynamics and the broader implications of Sino-American competition in the Indo-Pacific.